Cost-Effective Method to Perform SARS-CoV-2 Variant Surveillance: Detection of Alpha, Gamma, Lambda, Delta, Epsilon, and Zeta in Argentina - Torres, Carolina (2021)
The emergence of SARS-CoV-2 variants with concerning characteristics to public health has attracted the attention of the scientific community and governments both regionally and globally since the end of 2020. The most relevant variants described so far include: Alpha (lineage B.1.1.7), first detected in the United Kingdom; Beta (lineage B.1.351), initially detected in South Africa; Gamma (lineage P.1), initially detected in Manaus, Brazil, and Japan; Delta (lineage B.1.627.2), initially detected in India; Lambda (lineage C.37), initially detected in Peru; Mu (lineage B.1.621), first detected in Colombia; Epsilon (lineages B.1.427 and B.1.429), initially detected in California, United States; and Zeta (lineage P.2), first detected in Rio de Janeiro, Brazil (1). Four of these variants (Alpha to Delta) have been defined as variants of concern (VOCs) given their increased transmissibility and other characteristics, while Lambda and Mu have been defined as variants of interest (VOIs). The VOCs have also been associated with an increased risk of hospitalization (2, 3) and, in the case of Beta, Gamma, and Delta, with a moderate to a substantial reduction in neutralizing activity of monoclonal antibodies, convalescent, and vaccine sera (4–6). Gamma and Lambda are particularly relevant for Argentina due to their major presence in the South American region during the time of this study. Importantly, some of these variants share mutations in the Spike protein—several of them in the receptor-binding domain region—that potentially affect transmissibility, pathogenesis, and/or response to vaccination and immune-based therapies (7, 8). PAIS is the interinstitutional federal consortium of SARS-CoV-2 genomics in Argentina. It was created by the Ministry of Science and Technology to monitor SARS-CoV-2 diversity and evolution in the country, including surveillance of SARS-CoV-2 variants of public health interest (http://pais.qb.fcen.uba.ar/). The objective of this work was to implement a SARS-CoV-2 molecular surveillance strategy, in a context of limited resources, which allowed an assessment of the dynamic situation of circulation of viral variants, and at the same time, to perform genomic and evolutionary analyzes to study their origin and dispersion in our country.